Etiology and Viral Genotype in Patients with End-Stage Liver Diseases admitted to a Hepatology Unit in Colombia (2011)
ABSTRACT: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are the principal risk factor associated to end-stage liver diseases in the world. A study was carried out on end-stage liver disease cases admitted to an important hepatology unit in Medellin, the second largest city in Colombia. From 131 patients recruited in this prospective study, 71% of cases were diagnosed as cirrhosis, 12.2% as HCC, and 16.8% as cirrhosis and HCC. Regarding the risk factors of these patients, alcohol consumption was the most frequent (37.4%), followed by viral etiology (17.6%). Blood and/or hepatic tissue samples from patients with serological markers for HCV or HBV infection were characterized; on the basis of the phylogenetic analysis of HCV 5′ UTR and HBV S gene, isolates belonged to HCV/1 and HBV/F3, respectively. These results confirm the presence of strains associated with poor clinical outcome, in patients with liver disease in Colombia; additionally, HBV basal core promoter double mutant was identified in HCC cases. Here we show the first study of cirrhosis and/or HCC in Colombian and HBV and HCV molecular characterization of these patients. Viral aetiology was not the main risk factor in this cohort but alcohol consumption.